2003
DOI: 10.1177/030089160308900107
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Cystic Mesothelioma: A Case Series

Abstract: Background Cystic peritoneal mesothelioma is a rare disease associated with a favorable short-term prognosis. Longer follow-up documenting a persistence of symptoms and a high rate of recurrence after debulking surgery along with an uncertain natural history prompt a re-evaluation of prior treatment recommendations. No prior long-term clinical study of these patients is available. Methods The experience with five cases of cystic peritoneal mesothelioma, four females and one male, are reviewed. All of these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 10 publications
3
63
0
5
Order By: Relevance
“…We could only find 3 case reports of malignant transformation (González-Moreno et al, 2002;Mino et al, 2014;Sethna et al, 2003), one of which showed both benign and malignant cells within the same tumor, questioning whether the patient really had benign cystic mesothelioma which transformed, or a primary malignant process. Therefore, we see little added value of radical surgery with HIPEC in terms of prevention of malignant transformation.…”
Section: Resultsmentioning
confidence: 97%
“…We could only find 3 case reports of malignant transformation (González-Moreno et al, 2002;Mino et al, 2014;Sethna et al, 2003), one of which showed both benign and malignant cells within the same tumor, questioning whether the patient really had benign cystic mesothelioma which transformed, or a primary malignant process. Therefore, we see little added value of radical surgery with HIPEC in terms of prevention of malignant transformation.…”
Section: Resultsmentioning
confidence: 97%
“…However, only a small number of patients undergoing combined treatment has been reported in the literature. [14][15][16][17] Furthermore, the biology of peritoneal mesothelioma has been addressed only in recent years and the features of rare sub-variants, such as MCMP, are still largely unknown. The present paper reports the collaborative effort of two Italian centres to assess safety and effectiveness of the combined treatment.…”
Section: The Conceptual and Methodological Paradigm For The Managemenmentioning
confidence: 99%
“…[2,[11][12][13][14][15][16][17] This comprehensive strategy is successfully used to treat pseudomyxoma peritonei, a disease which shares with MCPM the low biological aggressiveness and tendency to recur after incomplete excision. [9,[14][15] In the current study, drugs were chosen for HIPEC based on their suitability to intra-peritoneal administration and synergistic effect with heat. No data are available on their activity against MCPM, although cisplatin and doxorubicin are largely used in systemic and local-regional treatment of peritoneal mesothelioma.…”
Section: Rational Basis For Comprehensive Treatment Of Multicystic Mementioning
confidence: 99%
See 1 more Smart Citation
“…Multicystic peritoneal mesothelioma (MPM) and WDPPM are exceedingly uncommon lesions with uncertain malignant potential and no uniform treatment strategy [26,27] . From the beginning of our peritoneal malignancies treatment program, MPM and WDPPM were included among the indications to cytoreduction and HIPEC, owing to their known potential to relapse and to evolve into aggressive malignant tumours [28] .…”
Section: Differentiated Papillary Peritoneal Mesothelioma (Wdppm)mentioning
confidence: 99%